SCREENING ON THE POTENTIAL BIOACTIVE COMPOUNDS OF ANTIBACTERIAL ACTIVITY IN SOFT CORAL COLLECTED FROM SOUTH BANGKA ISLAND WATERS AND LAMPUNG BAY - Rozirwan Rozirwan; Dietriech G Bengen; Neviaty P Zamani; Hefni Effendi; Chaidir Chaidir (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Soft corals contain bioactive compounds that can be used as a marine natural product. The puposes of this study was to determine of the soft corals inhibition potential for antibacterial activity. The methodology in this study included field sampling, extraction (in the solvent of n-hexane, ethyl acetate and methanol), antibacterial bioassay, and briefly describe the type of soft coral that possesed the highest inhibition. In sampling treatment, the biomass among wet samples and dry samples varied.  The highest shrinkage due to drying was found in Nephthea, followed by Lobophytum and Sarcophyton, while the lowest was found in the genus of Sinularia. Extracted from 12 samples of soft coral, the lowest extract weight was found in the semi-polar solvent (EtOAc), while the extract weight of n-Hex and MeOH was vary. Inhibition power from all extract samples was found on soft coral extract in the EtOAc and MeOH solvents. The highest value of inhibition power was found in soft coral of Sinularia polydactyla and S. Flexibilis within strong catogery.   Keywords: bioactive compounds, Lobophytum, Nephthea, Sarcophyton, Sinularia, soft coral